2015
DOI: 10.1177/1938640015569769
|View full text |Cite
|
Sign up to set email alerts
|

Role of Regional Anesthesia in Foot and Ankle Surgery

Abstract: Therapeutic, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 52 publications
(60 reference statements)
2
11
0
1
Order By: Relevance
“…Ankle joint arthrodesis was the most painful surgery in our analysis, and RA improved the combined PROs of pain (although still not to a satisfactory level), pain-related interference with mobilization and nausea more than in any other surgical category. These findings support recommendations to increase RA use in this type of surgery [15,16].…”
Section: Discussionsupporting
confidence: 82%
“…Ankle joint arthrodesis was the most painful surgery in our analysis, and RA improved the combined PROs of pain (although still not to a satisfactory level), pain-related interference with mobilization and nausea more than in any other surgical category. These findings support recommendations to increase RA use in this type of surgery [15,16].…”
Section: Discussionsupporting
confidence: 82%
“…However, no serious complication was seen in our patients. Likewise, previous studies used similar doses and found no systemic adverse effects ( 4 , 8 , 13 , 14 ). However, further studies are needed to determine the appropriate dose of local anesthetics for tourniquet pain tolerance.…”
Section: Discussionsupporting
confidence: 62%
“…The sciatic nerve block in the popliteal fossa can be used as a sole anesthetic method for foot or ankle procedures when a thigh tourniquet is not placed ( 3 ). It has been suggested that if needed, adding the femoral block to the popliteal block is effective in tolerating the thigh pain ( 4 , 5 ). However, the femoral block is insufficient to attenuate thigh pain ( 6 ), probably because it only anesthetizes the anteromedial surface of the thigh.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, below knee amputations are done with nerve blocks; however, if the incision extends above the knee, patients tend to complain of pain as blocks may be insufficient. [1] In our case, we administered combined lower limb blocks alone to manage a case of cellulitis with thrombocytopenia for above knee amputation.…”
Section: Introductionmentioning
confidence: 99%